The Effect of Quality of Work Life (QWL) and Motivation on Employee Performance at PT. Vulkatama Core - M. Ghandi Rukmana; Saiful Anwar (Trending: Jurnal Manajemen dan Ekonomi, 2025)
The purpose of this study is to examine the influence of quality of work life variables and motivation on employee performance at PT. Inti Vulkatama Padang. The type in this study uses a quantitative method, data collection through the distribution of questionnaires to 51 respondents using total sampling, namely non-random sampling techniques. By using instrument test tests (validity test and reliability test), classical assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis test with the help of the SPSS application. The results of the study show that the quality of work life has a positive and significant effect on employee performance, motivation does not have a positive and significant effect on employee performance.